Presynaptic Muscarinic Acetylcholine Receptors and TrkB Receptor Cooperate in the Elimination of Redundant Motor Nerve Terminals during Development - Nadal, Laura; Garcia, Neus; Hurtado, Erica; Simó, Anna; Tomàs, Marta; Lanuza, Maria A.; Cilleros, Victor; Tomàs, Josep (Frontiers in Aging Neuroscience, 2017)
The development of the nervous system involves the overproduction of synapses but connectivity is refined by Hebbian activity-dependent axonal competition. The newborn skeletal muscle fibers are polyinnervated but, at the end of the competition process, some days later, become innervated by a single axon. We used quantitative confocal imaging of the autofluorescent axons from transgenic B6.Cg-Tg (Thy1-YFP)16 Jrs/J mice to investigate the possible cooperation of the muscarinic autoreceptors (mAChR, M1-, M2- and M4-subtypes) and the TrkB receptor in the control of axonal elimination after the mice Levator auris longus muscle had been exposed to several selective antagonist of the corresponding receptor pathways in vivo. Our previous results show that M1, M2 and TrkB signalling individually increase axonal loss rate around P9. Here we show that although the M1 and TrkB receptors cooperate and add their respective individual effects to increase axonal elimination rate even more, the effect of the M2 receptor is largely independent of both M1 and TrkB receptors. Thus both, cooperative and non-cooperative signaling mechanisms contribute to developmental synapse elimination.